A NEW GENUS OF LONG-LEGGED CRICKETS FROM THE FORESTS OF EASTERN BRAZIL (ORTHOPTERA: GRYLLOIDEA: PHALANGOPSIDAE) - Mello, Francisco de A. G. de (REVISTA DE AGRICULTURA, 2015)
A NEW GENUS OF LONG-LEGGED CRICKETS FROM THE FORESTS OF EASTERN BRAZIL (ORTHOPTERA: GRYLLOIDEA: PHALANGOPSIDAE)